Performance evaluation of UAV-assisted cellular network using stochastic geometry-based model - Xin, Bee Wei; Muhammad, Nor Aishah; Saleh, Mohammed Mehdi; Anwar Apandi, Nur Ilyana (2023)
The deployment of unmanned aerial vehicles (UAVs) working as aerial base stations (ABSs) has appeared as a favorable solution due to its ability for quick deployment of communication links during emergency situations where wireless communication links via ground base stations (GBSs) are unavailable. This paper presents a stochastic-based geometry simulation approach for evaluating the coverage probability (CP) of a user that is served by the UAV base station within an isolated region where the GBSs are unable to function. The locations of the GBSs are assumed to be independently distributed in a 2D plane to form a homogeneous Poisson point process (PPP). User equipments (UEs) within the isolated region are served by the UAV hovering above the region's center. The simulation results are compared with the data obtained from the existing works to validate the simulation processes. The results demonstrate that increasing the height of the antenna and the radius of the isolated region leads to a decrease in the signal-to-interference ratio (SIR) CP. It is also found that SIR coverage can be improved by increasing the number of antenna elements.